STUDI PEMBANGUNAN FRAMEWORK BERORIENTASI OBJEK STUDI KASUS PEMBANGUNAN FRAMEWORK PENJADWALAN - -, Nur Afif (Teknosains, 2013)
framework can be defined as a âsemi-completeâ appication which can be reuse and specialized to produce many application in a specific domain.Building a framework is different from building other kind of software. It needs a special method. This method combines domain engineering and hot-spot driven framework development. Domain engineering is aimed to develop family of system in a domain, which is also suitable to developing framework. This writing also presents study about tools used in domain engineering such as feature modeling and domain specific language (DSL). The proposed method also using hot-spot driven framework development to identify hot-spots and frozen-spots of the framework by using tools such as hot-spot card and framework construction principle (FCP).Chosen case study for implementing the proposed method is scheduling domain. Scheduling was chosen because scheduling is a well-defined science and has many literature so is relatively easy to understands the domain. Scheduling also has many variety spots which is suitable to be implements as framework.Key word: reuse, domain engineering, hot-spot, frozen-spot, scheduling, flexibility.